Transient Receptor Potential Ankyrin 1 (TRPA1) Mediates Hydrogen Sulfide-induced Ca2+ Entry and Nitric Oxide Production in Human Cerebrovascular Endothelium - Soda, Teresa; Brunetti, Valentina; De Sarro, Giovambattista; Biella, Gerardo; Moccia, Francesco; Berra-Romani, Roberto; Scarpellino, Giorgia (Current Neuropharmacology, 2025)
IntroductionThe gasotransmitter hydrogen sulfide (H2S) modulates various brain functions, including neuron excitability, synaptic plasticity, and Ca2+ dynamics. Furthermore, H2S may stimulate nitric oxide (NO) release from cerebrovascular endothelial cells, thereby regulating NO-dependent endothelial functions, such as angiogenesis, vasorelaxation, and cerebral blood flow (CBF). However, the signaling pathway by which H2S induces NO release from cerebrovascular endothelial cells is still unclear.MethodsHerein, we exploited single-cell imaging of intracellular Ca2+, H2S, and NO levels to assess how H2S induces Ca2+-dependent NO release from the human cerebrovascular endothelial cell line, hCMEC/D3.ResultsAdministration of the H2S donor, sodium hydrosulfide (NaHS), induced a dose-dependent increase in (Ca2+)i only in the presence of extracellular Ca2+. NaHS-induced extracellular Ca2+ entry was mediated by the Ca2+-permeable TRPA1 channel, as shown by pharmacological and genetic manipulation of the TRPA1 protein. Furthermore, NaHS-dependent TRPA1 activation led to NO release that was abolished by buffering the concomitant increase in (Ca2+)i and inhibiting eNOS. Furthermore, the endothelial agonist, adenosine trisphosphate (ATP), caused a long-lasting elevation in (Ca2+)i that was driven by cystathionine γ-lyase (CSE)-dependent H2S production and by TRPA1 activation. Consistent with this, ATP-induced NO release was strongly reduced either by blocking CSE or by inhibiting TRPA1.ConclusionThese findings demonstrate for the time that H2S stimulates TRPA1 to induce NO production in human brain microvascular endothelial cells. Additionally, they show that this signaling pathway can be recruited by an endothelial agonist to modulate NO-dependent events at the human neurovascular unit.
Keywords: Hydrogen sulfide